The Tsaatans borderline life (based on field research) - Aiyzhy, Elena; КanunnikovDmitry; Mongush, Salbak; Mongush, Sayana (Opción, 2019)
This article is dedicated to a small group of reindeer herders of Khubsugulaimak of Mongolia the Tsaatans that preserve in the memory their common origin and relative relations with Todzha-Tuvans living Todzha Basinof the republic of Tuva. Two people separated since the Russian-Mongolian border was formed into the mountains of Eastern Sayan. The border isolates two people not only physically, but also in terms of culture - language, religion, material culture. It leads to the increasing changes in lifestyle, distance between the two groups of people. The border passed through the ground, language and consciousness.